2007
DOI: 10.1111/j.1365-2885.2007.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tilmicosin in equine tissues and plasma

Abstract: netics of tilmicosin in equine tissues and plasma. J. vet. Pharmacol. Therap. 31, 66-70.The macrolide antibiotic tilmicosin has potential for treating bacterial respiratory tract infections in horses. A pharmacokinetic study evaluated the disposition of tilmicosin in the horse after oral (4 mg ⁄ kg) or subcutaneous (s.c.) (10 mg ⁄ kg) administration. Tilmicosin was not detected in equine plasma or tissues after oral administration at this dose. With s.c. injection, tilmicosin concentrations reached a maximum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…These results demonstrated that this nanoparticle carrier remarkably reduced the acute toxicity of tilmicosin. The lower transient drug concentration of Til-HCO-SLN could account for the reduction of acute toxicity of tilmicosin [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrated that this nanoparticle carrier remarkably reduced the acute toxicity of tilmicosin. The lower transient drug concentration of Til-HCO-SLN could account for the reduction of acute toxicity of tilmicosin [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ineffectiveness of tilmicosin against infections may be related to inadequate therapeutic drug concentrations and/or an insufficient residence time of the antibiotic in the mammary gland [ 5 ]. Repeated administrations and high dose could enhance the clinical efficacy, but high doses of tilmicosin can result in acute cardiac toxicity in cattle and severe reactions at the injection sites such as vascular collapse and transient swelling caused by a transient high drug concentration [ 6 , 7 ]. The severity of the side effects is dose-dependent [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…After oral administration, it was difficult to maintain clinically relevant drug concentrations of trimethoprim in PELF as only half of the total drug concentrations measured in plasma were found in PELF and these depleted rapidly. (Table 3) Homogenised lung tissue Concentrations of tilmicosin in lung homogenates have been studied in foals treated either orally or subcutaneously (SC) (Clark et al, 2008). Tilmicosin was not detectable by HPLC in serum or tissues after oral dosing.…”
Section: Absorbent Discs/cotton Swabsmentioning
confidence: 98%
“…Cardiotoxicity of several antibiotics is widely known in donkeys. An example is tilmicosin, a macrolide commonly used in respiratory diseases in some species [22]. Doses used in horses (10 mg/kg) have been shown to induce transient and short-lasting changes in cardiac function and indexes measured by echocardiography in donkeys [23].…”
Section: Cardiovascular Systemmentioning
confidence: 99%